Synthesis, spectral studies and cytotoxicity of organotin(IV) complexes with hydrazone ligands - Nur Hafizah, bt Ramli (Universiti Malaysia Sarawak, UNIMAS, 2012)
Eight new organotin(IV) complexes of 2-hydroxy-3-methoxybenzaldehyde isonicotinylhydrazone [L1 (1)] with general formula [RnSnCl3-n (L1)] [ R = Me, n = 2 (3); R = Bu, n = 2 (4); R = Ph, n = 2 (5); R = Me, n = 1 (6); R = Bu, n = 1 (7); R= Ph, n= 1 (8)] were synthesized by direct reaction of the ligand (1), base and organotin(IV) chloride(s) in absolute methanol under N2 atmosphere. Another four organotin(IV) complexes of paminoacetophenone isonicotinylhydrazone [L2 (2)] with general formula [RnSnCl3-n] [ R = Me, n = 2 (9); R = Bu, n = 2 (10); R = Me, n = 1 (11); R = Ph, n = 1 (12)] were also synthesized by direct reaction of the ligand (2), base and organotin(IV) chloride(s). The ligands (1-2) and their organotin(IV) complexes (3-12) have been characterized by elemental analyses, UV-Visible, FT-IR and 1H NMR spectral studies. Spectroscopic data suggested that ligand (1) acted as a dinegative tridentate and ligand (2) acted as uninegative bidentate chelating agent. The toxicity of the hydrazone ligands (1-2) and their selected organotin(IV) complexes were evaluated against Artemia salina. The results shown that the selected organotin(IV) complexes have better cytotoxicity than the free ligands (1-2). Furthermore, it has been shown that diphenyltin(IV) complex exhibit significantly better activity than the other organotin derivatives.